First nontrivial group of homologies of simplicial schemes of unimodular frames over the Dedekind ring - Zainalov, B. R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We prove a theorem on generation of the first nontrivial group of homologies of a simplicial scheme of unimodular framesover the Dedekind ring by standard cycles.